The Use of Vedolizumab in Preventing Postoperative Recurrence of Crohn's Disease. Issue 3 (16th February 2018) - Yamada, Akihiro; Komaki, Yuga; Patel, Nayan; Komaki, Fukiko; Pekow, Joel; Dalal, Sushila; Cohen, Russell D; Cannon, Lisa; Umanskiy, Konstantin; Smith, Radhika; Hurst, Roger; Hyman, Neil; et al.
Abstract: Background: Clinical and endoscopic recurrence are common after surgery in Crohn's disease (CD). Vedolizumab has been increasingly used to treat CD, however, its effectiveness in preventing postoperative recurrence remains unknown. We aimed to investigate the use of vedolizumab in the postoperative setting and compare the risk of recurrence between patients receiving vedolizumab and anti-tumor necrosis factor (TNF)-α agents. Methods: Medical records of CD patients who underwent surgery between April 2014 and June 2016 were reviewed. We first analyzed how frequently vedolizumab is used to prevent postoperative recurrence and compared the patient characteristics with those being treated with other therapies. Furthermore, the rates of endoscopic remission, defined as a simple endoscopic score for CD of 0, at 6–12 months after surgery were compared between patients receiving vedolizumab and anti-TNF-α agents. Clinical, biological, and histologic outcomes such as Harvey-Bradshaw index, C-reactive protein, and histologic inflammation also were compared between the 2 groups. Risks of recurrence were assessed by univariate, multivariate, and propensity score-matched analyses. Results: Among 203 patients that underwent a CD related surgery, 22 patients received vedolizumab as postoperative treatment. There were 58, 38, and 16 patients who received anti-TNF-α agents, immunomodulators, and metronidazole, respectively, whereas 69 patients were monitored without any medication. Patients receiving vedolizumab were young and frequently had perianal disease. Patients postoperatively treated with vedolizumab or anti-TNF-α agents were mostly treated with the same agent pre- and postoperatively. Rate of endoscopic remission at 6–12 months in the vedolizumab group was 25%, which was significantly lower as compared to anti-TNF-α agent group (66%, P = 0.01). Vedolizumab use was the only factor that was associated with an increased risk of endoscopic recurrence on both univariate (odds ratio (OR) 5.58, 95% confidence interval (CI) 1.51–24.3, P = 0.005) and multivariate analysis (OR 5.77, 95%CI 1.71–19.4, P = 0.005). The results were supported by a propensity score-matched analysis demonstrating lower rates of endoscopic remission (25 vs 69%, P = 0.03) in patients treated with vedolizumab as compared to anti-TNF-α agents. Conclusion: In the present retrospective cohort study of real-world experience, vedolizumab was shown to be commonly used as postoperative treatment for CD especially in high risk patients. Multivariate and propensity score-matched analyses showed that postoperative endoscopic recurrence in CD was higher with vedolizumab than with anti-TNF-α agents, but further investigation including controlled trials is required before determining the utility of vedolizumab in preventing postoperative recurrence of CD.